2009
DOI: 10.1088/1748-6041/4/6/065002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of argon purity on mechanical properties, microstructure and fracture mode of commercially pure (cp) Ti and Ti-6Al-4V alloys for ceramometal dental prostheses

Abstract: Provision of an inert gas atmosphere with high-purity argon gas is recommended for preventing titanium castings from contamination although the effects of the level of argon purity on the mechanical properties and the clinical performance of Ti castings have not yet been investigated. The purpose of this study was to evaluate the effect of argon purity on the mechanical properties and microstructure of commercially pure (cp) Ti and Ti-6Al-4V alloys. The castings were made using either high-purity and/or indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Thus, an increase in C-contamination on the implant surface leads to a reduction in the surface energy (Wennerberg et al 2014). The Ti6Al4V-ELI alloy implant treated via sandblasting and acid etching is considered an excellent alternative for use in the manufacturing of small-diameter dental implants because of its improved mechanical strength compared with cpTi, in addition to their favorable clinical documentation in orthopedics (Bauer et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an increase in C-contamination on the implant surface leads to a reduction in the surface energy (Wennerberg et al 2014). The Ti6Al4V-ELI alloy implant treated via sandblasting and acid etching is considered an excellent alternative for use in the manufacturing of small-diameter dental implants because of its improved mechanical strength compared with cpTi, in addition to their favorable clinical documentation in orthopedics (Bauer et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…TiZr alloy has been recently introduced in the fi eld of implant dentistry for more challenging clinical situations, because it provides higher mechanical properties than cpTi grade 4 (Al- Nawas et al, 2011;Barter et al, 2011;Chiapasco et al, 2011). Nevertheless, Ti6Al4V implants could also be used for small diameter dental implants because of improved mechanical strength when compared to cpTi and because of their favourable clinical documentation in orthopaedics (Bauer et al, 2009). All three implant surfaces used in the present study demonstrated moderate roughness values comparable to other contemporary implant systems (Wennerberg and Albrektsson, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…11 Machines that associate a controlled environment with inert gas as a heat source may be able to reduce the contamination of alloy. 12 In addition, they allow the temperature to be controlled, with the technical advantage of reducing heating time and eliminating the need for flame adjustment. Moreover, there is reduced contamination, less probability of burning the metal, and consequently, less porosity due to volatilization of components with low melting temperatures.…”
Section: Introductionmentioning
confidence: 99%